Overview of evidence-based research on acupuncture for stroke treatment using magnetic resonance imaging technology - Ke, Chao; Shi, Wenying; Zhou, Zhuo; Xie, Zhengrong; Sun, Mengzi; Yu, Juli; Shan, Shengtao; Zhang, Wei (Frontiers in Neuroscience, 2024)
BackgroundStroke is a neurological condition characterized by high rates of disability and mortality. Magnetic resonance imaging (MRI) is widely used to examine the mechanisms of acupuncture in stroke treatment.PurposeThis review provides neuroimaging evidence for the efficacy of acupuncture in treating stroke using MRI.MethodWe conducted a comprehensive search of databases, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan Fang Data, Chinese BioMedical Literature Database (CBM), and Chonqing VIP (CQVIP), from inception to April 2024. Relevant neuroimaging studies on acupuncture for stroke were included, and the research findings were presented through charts and textual analyses.ResultsA total of 158 studies were included, and the overall methodological quality of the included studies was moderate to high. The results were divided into three categories: basic characteristics, clinical characteristics, and quality assessment of the included literature.ConclusionWe elucidated the neural mechanisms underlying the effects of acupuncture on stroke; however, the evidence remains preliminary. There is a need for large-scale, well-designed, multimodal neuroimaging trials. This review represents the first active use of an evidence map to systematically review and illustrate the current state of neuroimaging research on the acupuncture treatment of stroke, thereby providing a valuable reference for future research.